Potential entrepreneurs transition from corporate organisations: the relationships of organisational culture and entrepreneurial motivation. (2nd August 2019) - Adamu, Muhammad
The aim of this research is to examine the influence of organisational culture and entrepreneurial motivation on potential entrepreneurs in corporate organisations. Quantitative technique was employed through a cross-sectional survey where primary data has been collected for the study. Correlation coefficients were used, and the study findings suggested that organisational culture and entrepreneurial motivation significantly influences corporate effectiveness. Furthermore, this study theoretically incorporates the VEMT and SCTOP especially in developing the conceptual framework. The merging of these theories explicates the novelty of this study also, exploring the under-researched self-employment determinants in the context of Nigeria added value to the entrepreneurship literature.